The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5114/hpr.2017.65206
|View full text |Cite
|
Sign up to set email alerts
|

Personal and familial predictors of depressive feelings in people with orthopedic disability

Abstract: People with orthopedic disability experience limitations in physical ability, which can cause psychological problems such as depressive feelings. This paper investigates the role of family environment, caregiver characteristics, and personal resources in the acceptance of disability and depressive feelings of persons with orthopedic disability. participants and procedureData were collected from 161 Turkish people with orthopedic disability (mean age = 35.60 years, SD = 10.18) and their family caregivers (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 70 publications
0
6
1
Order By: Relevance
“…The health and well-being of caregivers and the people they take care of were also affected by certain situations such as the existence of family conflicts, the presence of a hostile attitude, or the lack of warmth in the family nucleus [ 60 , 61 ]. Both hostile attitude and lack of warmth were measured through the Family Assessment Device (FAD) [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The health and well-being of caregivers and the people they take care of were also affected by certain situations such as the existence of family conflicts, the presence of a hostile attitude, or the lack of warmth in the family nucleus [ 60 , 61 ]. Both hostile attitude and lack of warmth were measured through the Family Assessment Device (FAD) [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Taking care of these people also has a large impact on other areas of their caregivers’ lives. Eight of the studies [ 22 , 34 , 44 , 60 , 63 , 66 , 67 , 68 ] showed that coping with this situation implies that many caregivers have to leave paid jobs in order to devote themselves fully to care, thus facing significant financial problems, which directly affects their well-being. Many caregivers find it impossible to reconcile work and family due to the high demands placed on the person receiving care.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations